Electrochemical Co-deposition of Polydopamine/Hyaluronic Acid for Anti-biofouling Bioelectrodes - Kim, Semin; Lee, Sanghun; Park, Junggeon; Lee, Jae Young (Frontiers in Chemistry, 2019)
Bioelectrodes are key components of electronic devices that efficiently mediate electrical signals in biological systems. However, conventional bioelectrodes often undergo biofouling associated with non-specific proteins and cell adhesion on the electrode surfaces, which leads to seriously degraded electrical and/or electrochemical properties. Hence, a facile and effective method to modify the surface of bioelectrodes is required to introduce anti biofouling properties and improve performance. Here, we report an electrochemical surface modification of a bioelectrode via co-deposition of hyaluronic acid (HA) and polydopamine (PDA). The electrochemical polymerization and deposition of PDA offered simple and effect incorporation of highly hydrophilic and anti-fouling HA to the electrode surfaces, with no substantial increase in impedance. HA-incorporated PDA (PDA/HA)-modified electrodes displayed significant resistance to non-specific protein adsorption and the adhesion of fibroblasts. In addition, 4-week subcutaneous implantation studies revealed that the modified electrodes attenuated scar tissue formation compared with that induced by unmodified bare electrodes. This simple and effective electrochemical surface modification could be further employed for various implantable bioelectrodes (e.g., prosthetics and biosensors) and could extend their bioelectronic applications.